Atlas of clinical diagnosis / M. Afzal Mir - Mir, M. Afzal
The traditional teaching of clinical medicine by the bedside, by lectures, tutorials and through textbooks is mainly system- and disease-oriented. Diseases are presented under their relevant system headings and all the clinical manifestations, irrespective of their regional and anatomical diversity, are presented under each disease. This discipline of learning clinical medicine is contrary to how it is practised in real life, where the history and examination may have to be constructed on a single symptom or an asymptomatic sign. The patient presents with one or more symptoms and the examiner, during history-taking and clinical examination, takes note of various signs that are present and constructs a diagnosis from these